Sosialisasi Olahraga Petanque Pada Masyarakat Di Desa Hepulawa Kecamatan Limboto, Kabupaten Gorontalo - Duhe, Edy Dharma Putra; Prasetyo, Agung; Sari, Permata; Kadir, Suprianto (Jambura Arena Pengabdian, 2024)
One activity that supports individual health and social relationships is sports. Sports play an essential role in community life as they not only maintain physical fitness but also strengthen social bonds and create a sense of togetherness. There are some lesser-known sports, one of which is Petanque. The purpose of this initiative is to socialize and introduce the sport of Petanque in Hepulawa Village, increase community participation in sports activities, and develop Petanque playing skills. The stages of this initiative include preparation, implementation, and evaluation of the process and results. This activity was conducted at the Hepulawa Village Field, involving 50 participants from various age groups. The results showed a significant increase in participants' knowledge and skills in playing Petanque, with approximately 95% of participants able to explain the basics of the game and 40% mastering the basic techniques after one training session. The high level of enthusiasm and participation reflects a great interest in this sport and indicates that this activity successfully attracted the attention and active involvement of various community members. Additionally, this activity succeeded in strengthening social relations among village residents, creating a sense of togetherness, and reducing dependence on technology and gadgets. Therefore, Hepulawa Village is expected to become a pioneer in the development of Petanque in Limboto District and its surroundings.